Use of the TRAC PAC as a microcomputer-based laboratory (MBL) tool for addressing misconceptions in kinematics and kinematic graphs held by secondary school learners - Green, W. J.(Whitfield James) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2004.